Training and Assistance for the Development of PjBL Teaching Materials Based on Strengthening the Pancasila Profile for Elementary School Teachers - Suryaningsih, Sri; Arwan, Arwan; Supriyanto, Try; Lestari, Ayu Citra; Rahma, Nur’aini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Training and mentoring in the preparation of project-based learning materials (Project-Based Learning/PjBL) which focuses on strengthening the profile of Pancasila students aims to improve the understanding and skills of teachers at SDN 1 Kaleo in implementing the independence curriculum. This program consists of several stages: socialization, training, application of e-book technology, mentoring, and evaluation involving 21 teachers. The results showed a significant increase in teachers' understanding of the Pancasila student profile from 53.8% to 95.2%, understanding of the PjBL model from 51.6% to 97.3%, and teaching materials from 54.3% to 98.3%. The introduction of e-books as an innovation in teaching materials supports independent learning, especially for students with limited school attendance. Although there were challenges in selecting relevant projects and using e-books, the focus group discussion (FGD) approach and intensive mentoring helped overcome these challenges. This training opens up opportunities for SDN 1 Kaleo to become a training model for other schools, thus expanding the positive impact of this program. Thus, this research has succeeded in increasing teachers' capacity to support the independent curriculum and forming a young generation with character according to the profile of Pancasila students.